Factors that Influence the Dissemination of Knowledge in Technology Transfer among Malaysian Manufacturing Employees - Sahadevan, Mughaneswari ap; Jedin, Mohd Haniff (UI Scholars Hub, 2014)
The meaning of technology transfer is so wide but mostly involving some form of technology-related exchange. However, in this particular paper, technology transfer is consider as a concept to examine the process of disseminating knowledge and skills that a person owned to another person in order to generate higher productivity with new approach of producing a particular product or service. Although, many researchers have explored the evolution of technology transfer, nonetheless some drivers are yet to be explored in a Malaysian manufacturing industry. This study, therefore attempts to determine the relationship between absorptive capacity, transfer capacity, communication motivation and learning intent and technology transfer performance. A survey methodology was used in a Japanese multinational company based in Klang Valley, Malaysia. A total of 117 questionnaires were received. Results show that absorptive capacity is the most significant to influence technology transfer performance.